Ethnopharmacology and scientific validation of antidiarrheal plants used by the Osing Tribe in Banyuwangi, Indonesia - KHRISNA AGUNG CENDEKIAWAN; KINTOKO KINTOKO; SAPTO YULIANI; FIRDHA APRILLIA WARDHANI (Society for Indonesian Biodiversity, 2026)
Abstract. Cendekiawan KA, Kintoko, Yuliani S, Wardhani FA. 2026. Ethnopharmacology and scientific validation of antidiarrheal plants used by the Osing Tribe in Banyuwangi, Indonesia. Biodiversitas 27 (2): d270229. https://doi.org/10.13057/biodiv/d270229. Indonesia has a rich heritage of medicinal plant use; however, much of this traditional knowledge, especially among indigenous communities such as the Osing people in East Java, remains undocumented. This study aimed to explore the antidiarrheal plants used by the Osing community through an ethnopharmacological survey and scientific validation. Data were collected through structured interviews with local informants in Banjar and Licin Villages, Licin Sub-district, and Banyuwangi District. Use value (UV) and fidelity level (FL) indices were calculated to assess the cultural significance and therapeutic relevance of each species. Phytochemical screening and liquid chromatography-mass spectrometry (LC-MS) were conducted to identify bioactive compounds. The most frequently reported species were Psidium guajava (UV = 2.44; FL = 64.7%) and Piper betle (UV = 1.11). LC-MS analysis confirmed the presence of major secondary metabolites, including quercetin and kaempferol, which are known for their pharmacological activity in the treatment of gastrointestinal disorders. Scientific validation in this study also incorporated in silico approaches, including Lipinski’s Rule of five evaluation to assess drug-likeness, ADMET profiling to predict pharmacokinetic and toxicity parameters, and molecular docking to explore the binding interactions of identified phytoconstituents with antidiarrheal target proteins. Quercetin demonstrated strong binding affinity (ΔG = -9.72) and an acceptable RMSD value (1.83 Å). A TPC value of 0.2357 was obtained from a mixture containing 0.84 g of P. guajava and 0.18 g of P. betle. The antioxidant activity, measured as IC50, was 7.51 µg/mL. These findings suggest that quercetin holds strong potential as a lead compound for antidiarrheal drug development. Overall, this study highlights the scientific value of traditional knowledge and encourages further investigation into plant-based treatments for gastrointestinal disorders.